The role of the organizational force of deans of physical education and sports sciences colleges in Iraqi universities from the point of view of teaching - KARIM RAHMAN, AUDAI (International Journal of Psychosocial Rehabilitation, 2020)
The faculties of physical and sports sciences witnessed a remarkable expansion in Iraqi universities as a result of following the method of development and development of practical aspects in the plans and programs of ministries as well as as the result of the expansion of the admission of students and disciplines required to reach the promotion of the qualified human element as one of the most important elements of construction and sophistication by looking the college as a collective effort to achieve a common goal, which makes the need for business guidance and the provision of services to cared for and the development of plans and programs necessary to achieve this goal from here The role of deanship the college is represented by the person of the Dean as a key source in the process of leadership and implementation of programs and plays a key role in all the skills that accompany the organizational and administrative work as well as the method of activities and follow up the relationship between the existing joints as well as note the relationship the external environment as one of the important tributaries of requirements of work and this requires that there be factors that are outrageous to contribute to the process of developing plans and programs and be A sustainable base in the work by noting and following up all the directives and instructions issued and the extent to which the workers are committed to implementing them according to what is required and this highlights the role of concepts that accompany the administrative work, especially for the main leaders as the key leader in the process of leadership and implementation, including the concept of organizational power, which is considered an administrative concept that enhances the position of the main leaders by studying the place of strength and injustice in the work and diagnosing their knowledge in order to address them and reach a kind of adaptation to all directions and instructions Issued through the follow-up and use of the principle of participatory relationship in the work as well as the use of the principle of reward and punishment has an impact on the development of incentives among workers, especially as we are witnessing a kind of development at all levels of the provision of modern means of communication that enriches scientific experiments and provides them with information that leads to the development of methods of work and hence comes importance through.